Separation of Plastic Particles in Electrostatic Field Produced by Electrodes of Optimized Shape - Frantisek Mach; Pavel Kus; Pavel Karban; Ivo Dolezel (Communications - Scientific letters of the University of Zilina, 2013)
Shape optimization of electrodes for the device for electrostatic separation of triboelectrically charged plastic particles is carried out. The objective function maximizes the efficiency of separation consisting in the highest possible number of particles falling down to the prescribed bins. Electric field in the system is solved numerically, using the fully adaptive higher-order finite element method. The movement of particles in the device influenced by the Coulomb force is determined by means of an adaptive Runge-Kutta-Fehlberg method with a time varying time step. The shape optimization is carried out using a technique based on genetic algorithms. The methodology is illustrated by an example whose results are discussed.